Relación entre las actitudes maternas y los niveles de ansiedad que presentan las madres de un establecimiento penitenciario de Lima Metropolitana - Romero Gutierrez, Andrea de Stefanía (2020)
The purpose of the following investigation is to determine the correlation between maternal attitudes (acceptance, over-protection, over-indulgence, rejection) and the levels of anxiety in recluse mothers in a prison in Metropolitan Lima. The sample was constituted by 98 incarcerated mothers, who had children between the ages of 0 and 3 years inside or outside the prison, and the sampling type was non-probabilistic-for convenience. The design of the study was Descriptive-Correlational. As a result we found a correlation coefficient of ,469, which means there is a moderated relation between the variables; because motherhood as biological and psychological process implies changes in the emotional state of the mother. For the specific objectives we found a correlation coefficient of de ,0235 (acceptance); ,1295 (over-protection); ,0678 (over-indulgence); ,0762 (rejection). Also, there is a difference of 1.57 in the medias of the anxiety levels in mothers with children inside and outside the prison, being the anxiety levels in mothers with their child outside superior to the ones who have their child inside with them. Finally, we found that the prevalent attitudes in the inmates was acceptance.